A novel hydnoid species of Hydnellum (Bankeraceae, Thelephorales) from southwest China - Lei, Lei; Luangharn, Thatsanee; Yu, Feng-Ming; Li, Wei-Jiao; Zhao, Qi (Phytotaxa, 2023)
Hydnellum (Bankeraceae, Thelephorales) is a stipitate hydnoid genus with spinous hymenophore, brown tuberculate basidiospores, and very tough, corky, or leathery flesh. This genus is widely distributed in the northern hemisphere, and many species are committed to mycorrhizal relationships with certain trees. In this study, one new species of Hydnellum, H. ailaoense sp. nov., was proposed, described and illustrated here. Its phylogenetic position was evaluated using two genomic loci (nLSU and ITS). The phylogenetic result shows that H. ailaoense and H. underwoodii group together and form a sister branch with a strong support value. Morphologically, H. ailaoense differs from other Hydnellum members in its pileus uplifted squamosa, margin brownish beige to grey, and the tuberculi of basidiospores usually isolated or grouped in 2 or more.